G259 Novel treatment option of Sirolimus ointment for facial angiofibromas in individuals with Tuberous Sclerosis Complex (TSC). (27th April 2016) - Amin, S; Lux, A; O'Callaghan, F
Abstract : Introduction: Facial angiofibromas afflict 80–90% of patients with TSC. They can cause recurrent bleeding and facial disfigurement, and they are associated with high psychological morbidity for these patients – especially in the 50% of patients with normal intellect. In recent years, systemic mTOR inhibitors (Sirolimus and Everolimus) have been used to treat the complications of TSC but their use has been limited because of concerns about systemic side effects. This is the first study to assess the efficacy and safety of Rapamycin ointment on facial angiofibromas in TSC using a standardised and validated facial angiofibromas severity index (FASI). We also assessed quality of life. Methods: In this prospective pilot study, we recruited 14 patients with a definite diagnosis of TSC from our clinic in Bath. The impact of a 6-month course of Sirolimus ointment 0.1% was assessed using digital photography and blinded dermatological review, and using the Facial Angiofibroma Severity Index (FASI). The quality of life scores, using PedsQL for children and SF36 for adults, were also assessed at the end of the 6 months. Linear regression and paired t -tests were used to analyse the data. Results: FASI scores were improved in ten out of fourteen patients (71%) P = <0.001. Of the remaining four patients, three had improvement in rash but no FASI score change. One did not respond. None of the patients had progression or worsening of their rash. All the children showed improvement, in contrast to only two out of six (33%) adults, P = 0.006. Linear regression analysis showed that the response rate reduces with increasing age (correlation coefficient -0.1, P = 0.01). Learning difficulties or gender difference had no detectable influence on the outcomes. Proxy-reported PedsQL scores for total psychosocial domain improved significantly with treatment p = 0.015. Conclusions: Sirolimus ointment 0.1% administered once a day appears to be effective in treating facial angiofibromas, as well as safe and well tolerated. This treatment has a positive significant impact on patients' quality of life. It is more effective in children than adults and therefore early treatment appears to add greater benefit.